COMPARATIVE ANALYSIS OF BRAND EQUITY BETWEEN SALES PROMOTION AND SOCIAL MEDIA MARKETING ON SPORTSWEAR IN MANADO - Tayuyung, Adventus Christ; Lapianlan, S L. H. V. J,; Tielung, Maria V. J. (Universitas Sam Ratulangi, 2021)
Brand is very significant to become a market leader because of the conditions of increasingly fierce business competition. Brand equity can increase or decrease the production value for consumers. With strong brand equity, the marketer's goal of always developing and capturing the market will be easier to achieve. According to this statement, itâ€™s described that marketing activities also affect brand equity. This research aims to discover is there any significant effect in Sportswear Brand Equity between Sales Promotion marketing technique compare with Social Media Marketing in Manado. This research is quantitative research which uses Brand Awareness, Brand Loyalty, Brand Association, Perceived Quality and Other Proprietary Assets as the indicators for this research. The sample is 100 respondents. While to know the differences between the two marketing strategies, this research uses Independent Sample t-Test as the analytical tool. Based on the analysis of the data collection instruments, the result of this research in there are a significance differences between Sales Promotion and Social Media Marketing that affect the Brand Equity of Sportswear in Manado. From the results, it is recommended for these two marketing strategies to develop the brand equity of a company.Â Keywords: brand equity, sales promotion, social media marketing, brand awareness, brand loyalty, brand association,